Metal accumulation by submerged macrophytes in eutrophic lakes at the watershed scale - Xing, Wei; Wu, Haoping; Hao, Beibei; Liu, Guihua (Environmental science and pollution research international, 2013)
Metal concentrations (Al, Ba, Ca, K, Li, Mg, Na, Se, Sr and Ti) in submerged macrophytes and corresponding water and sediments were studied in 24 eutrophic lakes along the middle and lower reaches of the Yangtze River (China). Results showed that these eutrophic lakes have high metal concentrations in both water and sediments because of human activities. Average concentrations of Al and Na in tissues of submerged macrophytes were very high in sampled eutrophic lakes. By comparison, Ceratophyllum demersum and Najas marina accumulated more metals (e.g. Ba, Ca, K, Mg, Na, Sr and Ti). Strong positive correlations were found between metal concentrations in tissues of submerged macrophytes, probably because of co-accumulation of metals. The concentrations of Li, Mg, Na and Sr in tissues of submerged macrophytes significantly correlated with their corresponding water values, but not sediment values.